"It Got Likes, But I Don't Think People Understood": A Qualitative Study of Adolescent Experiences Discussing Type 1 Diabetes on Social Media. (July 2022) - Chalmers, Kristen; Smith, Mia; Moreno, Megan; Malik, Faisal
Background: The majority of adolescents with type 1 diabetes (T1D) integrate social media engagement into their daily lives. The aim of this study was to explore adolescents' experiences and perspectives discussing their T1D on social media. Methods: Semi-structured interviews with adolescents with T1D were conducted in person and via telephone. Questions focused on the participant's experiences utilizing social media to discuss T1D and factors that informed the nature of T1D-related social media engagement. Open coding and thematic content analysis were used to identify emergent themes that aligned with accepted domains of social media affordances. Results: Participants included 35 adolescents with T1D. Adolescents' experiences related to discussing T1D on social media aligned with four affordances of social media: identity, cognitive, emotional, and social. The identity affordances of social media platforms allowed adolescents to curate online personas that selectively included their diagnosis of T1D, while managing the potential negative emotional and social implications linked to the stigma of T1D. Adolescents who decided to discuss T1D on social media leveraged cognitive affordances by providing and receiving diabetes management advice, emotional affordances by obtaining affirmation from peers, and social affordances by extending their network to include other individuals with T1D. Conclusions: Adolescents with T1D flexibly leverage the affordances offered by social media to access emotional support, information, and identity affirmation resources while navigating stigma-based social consequences. Our findings highlight the value of developing tools to support adolescents with T1D in comfortably discussing and receiving appropriate support about T1D on social media.